Evaluation of cosmetic creams containing Black cumin (Nigella sativa)-Lemon balm (Melissa officinalis L.)-Aloe vera (Aloe barbadensis miller) essences by modeling with Box Behnken method in Design Expert - Turedi, Ece; Acarali, Nil (ELSEVIER, 2022)
In this investigation regarding medicinal and aromatic plants, an experimental study was conducted on the effectiveness of black cumin, lemon balm and Aloe vera essences in cosmetic creams, which were selected for their beneficial biological activities such as anti-inflammatory, moisturizing etc. In line with this study stability test, which was important in the quality evaluation of cosmetic products, was carried out. Cream samples containing different concentrations of black cumin and lemon balm essences were kept at under 3 different temperature conditions as 0 degrees C, 25 degrees C and 40 degrees C and the necessary values were recorded. In this direction, the effects of the temperature on the physical and chemical properties of the cosmetic creams were assessed. Homogenization and colors as physical properties and pH value of the herbal cream samples were examined. It was observed that the pH value, which was an important parameter for skin care products, was 6.5 under the optimum experimental condition and it was an acceptable value for skin creams according to the literature. In the second part of the experimental study, the effect of the essence obtained from the Aloe vera plant on the samples was tested with the optimum condition selected from 17 different experimental sets by using the Design Expert optimization application. In addition, from the production of cosmetic products; it was necessary to pay attention to the environmental conditions stipulated in storage, transportation, and sales points. As a result of the tests, it was seen that the medicinal and aromatic plants used could be evaluated in the field of cosmetics and successful results could be obtained.
Keywords: Aloe vera; Black cumin; Cosmetic cream; Lemon balm; Box-Behnken design; Agriculture